1980
DOI: 10.4992/psycholres1954.22.7
|View full text |Cite
|
Sign up to set email alerts
|

Imitative Choice Behavior in Guppies

Abstract: In a two choice situation guppies were tested to see if they would tend to follow, without manifest reinforcement, the proficient(s) which had been avoidance trained to swim, and also if they could, when responding alone, behave in the same way as the proficients to follow the same cue-light that had guided the proficients' choice behavior.In Experiment I, the effect of the number of proficients was examined. The results indicated that increasing the number of proficients enhanced not only the following respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 13 publications
(9 reference statements)
2
23
0
Order By: Relevance
“…Thus in a constant, or slowly changing, environment, it is unlikely that matadaptive patterns will persist, and it is consequently unlikely that social learning will produce populations that differ in behavior with one behaving less adaptively than another. This reasoning is consistent with the findings of several studies of fish populations that the presence of conspedfics accelerates the learning of novel tasks or die effidency of foraging (Pitcher et al, 1982; Pitcher and House, 1987;Sugita, 1980;Welty, 1934). However, in a changing environment, socially transmitted traditions may constantly trail behind die environmental state because there may not be enough time to adjust to the optimal before a new behavior pattern becomes best.…”
Section: Figuresupporting
confidence: 89%
“…Thus in a constant, or slowly changing, environment, it is unlikely that matadaptive patterns will persist, and it is consequently unlikely that social learning will produce populations that differ in behavior with one behaving less adaptively than another. This reasoning is consistent with the findings of several studies of fish populations that the presence of conspedfics accelerates the learning of novel tasks or die effidency of foraging (Pitcher et al, 1982; Pitcher and House, 1987;Sugita, 1980;Welty, 1934). However, in a changing environment, socially transmitted traditions may constantly trail behind die environmental state because there may not be enough time to adjust to the optimal before a new behavior pattern becomes best.…”
Section: Figuresupporting
confidence: 89%
“…These findings suggest that much animal social learning should involve individual adoption of the behavior of the majority-that is, a copy-the-majority strategy. Although few empirical studies on animals have addressed this issue directly, social learning in which the probability of adopting a pattern of behavior increases with the proportion of demonstrators occurs in guppies (Lachlan, Crooks, & Laland, 1998;Laland & Williams, 1997;Sugita, 1980), rats (Beck & Galef, 1989;Chou & Richerson, 1992), pigeons (Lefebvre & , and humans (see Richerson, 1985, andHenrich, 2001, for reviews). Strictly speaking, this work provides only weak evidence of conformity, since the experiments would need to demonstrate a disproportionate tendency to adopt the behavior of the majority rather than a linear association between the probability of learning and the proportion of demonstrators exhibiting the behavior.…”
Section: "Who" Strategiesmentioning
confidence: 99%
“…Magurran & Higham (1988) reported that minnows (P. phoxinus) decreased their activity (an antipredatory response to reduce conspicuousness) after observing the startle responses of predator-inspecting group mates, indicating that antipredator information is transmitted between individuals. Moreover, investigations into the avoidance responses of guppies and zebrafish to artificial predators (Sugita 1980;Brown & Laland 2002a;Lindeyer & Reader 2010) suggest that the learning of specific antipredator behaviour is possible. Sugita (1980) found that guppies (Poecilia reticulata, Poeciliidae) learn to avoid an electric shock by following demonstrator fish into one of two safe compartments in a shuttle box.…”
Section: Antipredator Behaviourmentioning
confidence: 99%